Limitations of Classical Legal System Theory in Explaining the Complexity of Modern Regulation: Toward an Adaptive and Reflexive Legal Model - Haristov Aszadha; Saefullah (Jurnal Kewarganegaraan, 2026)
The complexity of modern regulation demonstrates that law can no longer be understood merely as a set of norms operating linearly through formal institutions. Technological development, institutional fragmentation, overlapping norms, sectoral interdependence, and rapid social change have transformed regulation into a complex, dynamic, and often unpredictable system. This article aims to analyze the limitations of classical legal system theory, particularly Lawrence M. Friedman’s framework of legal structure, legal substance, and legal culture, in explaining the complexity of modern regulation. This study employs normative legal research using conceptual, statutory, and theoretical approaches. The article argues that classical legal system theory remains important as an analytical foundation, but it is insufficient to explain the non-linear, adaptive, and cross-sectoral dynamics of contemporary regulation. Therefore, this article proposes an original conceptual framework called the Adaptive and Reflexive Law Model, which integrates legal system theory, social systems theory, complexity theory, legal complexity, reflexive law, and adaptive regulation. This model emphasizes normative coherence, institutional coordination, social responsiveness, feedback-based evaluation, regulatory complexity management, public participation, adaptive regulatory capacity, as well as legitimacy and legal certainty.